2009
DOI: 10.1159/000219385
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiological Study of Hepatitis Viruses in Ismailia, Egypt

Abstract: The hepatitis virus is hyperendemic in Egypt, western Asia and Africa. In Egypt, most studies have been carried out in the regions of the upper and lower Nile Delta, and so little is known about other parts of the country. Our project aimed to clarify the carrier rate of various hepatitis viruses in the northeastern province of Ismailia. A total of 214 patients with elevated liver enzymes were enrolled in this study. Sera were collected in Ismailia hospital. We conducted a serological and molecular-based surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 97 publications
4
15
0
Order By: Relevance
“…In Ismailia, using direct sequencing and phylogenetic analysis of the HCV NS5B gene, 15 cases (78.9%) were subtype 4a, two(10.5%) were subtype 1g, and one (5.2%) was related to subtype 4o (24). …”
Section: Discussionmentioning
confidence: 99%
“…In Ismailia, using direct sequencing and phylogenetic analysis of the HCV NS5B gene, 15 cases (78.9%) were subtype 4a, two(10.5%) were subtype 1g, and one (5.2%) was related to subtype 4o (24). …”
Section: Discussionmentioning
confidence: 99%
“…This relationship was subsequently confirmed by comparing patients infected with genotype 3 and those infected with other genotypes [14][15][16]. However, Genotype 4a represents more than 93 % of chronic HCV patients in Egypt [17][18]. …”
Section: Introductionmentioning
confidence: 96%
“…3 Diabetes is a marker for increased risk of HBV transmission through exposure to contaminated blood during diabetes care and monitoring. One study found that adults between 23 and 59 y of age with diabetes who lacked traditional risk factors for HBV infection had twice the odds of acquiring acute hepatitis B (HB) compared with adults without diabetes.…”
Section: Introductionmentioning
confidence: 99%